The significance of the correlation between the cell proliferative index KI-67 and the human epidermal growth factor HER2 in breast cancer patients who received neoadjuvant therapy. - Živković, Ognjen; Milićević, Anđela; Petrović, Ivana; Rakočević, Jelena; Inić, Zorka; Tatić, Svetislav; Dunđerović, Duško; Oprić, Dejan; Labudović Borović, Milica; Ristić, Svetlana; Buta, Marko (PONS - medicinski časopis, 2024)
Objective. Evaluation of the value of HER2 and Ki-67 expression and determination of their mutual correlation within two-factor analysis models in patients with a pathohistologically confirmed diagnosis of breast cancer, who received neoadjuvant therapy. Methods. The retrospective study includes all breast cancer patients who underwent neoadjuvant and surgical therapy at Serbia’s Institute of Oncology and Radiology between 2017 and 2019. HER2 positive status was defined either as a value of 3+ by immunohistochemical analysis or as an amplification of the HER2 gene by in situ hybridization, for values ​​of 2+. Relevant statistical methods were used to test statistical differences: chi-square test, Mann-Whitney U test, and Kruskall Wallis H-test. Results. In the analyzed group of patients, the most frequently determined value of HER2 expression is 1+. By testing the correlation of the Ki-67 cell proliferative index value with HER2 and testing the differences between groups by post hoc analysis on the material obtained by preoperative, core needle biopsy, a statistically significant difference was determined (H=9.020, p=0.029), especially between the HER2 groups (1+) and (3+) (highly statistically significant difference (U=863.5, p=0.005)) and HER2 (2+) and (3+) (statistically significant difference (U=907, p=.036)). Conclusion. The results of our study indicate that the degree of HER2 expression is in a statistically significant and positive correlation with the values ​​of the cell proliferative index Ki-67, which correlates with the results of previous studies and oncological practice, which confirmed that excessive amplification or expression of HER2 is associated with the degree of malignancy and poor prognosis of breast cancer.